The Effects of Compliance with Nutritional Counselling on Body Composition Parameters in Head and Neck Cancer Patients under Radiotherapy - D. Hopanci Bicakli; O. Ozkaya Akagunduz; R. Meseri Dalak; M. Esassolak; R. Uslu; M. Uyar (Journal of Nutrition and Metabolism)
Background. Radiotherapy (RT) has been associated with increased risk of malnutrition in cancer patients, particularly in those with head and neck cancer (HNC). The aim of this prospective study was to evaluate the effects of compliance of patients with individual dietary counselling on body composition parameters in HNC patients under RT. Material and Methods. Sixty-nine consecutive patients (mean age: 61.0±13.8) were prospectively followed. Bioelectrical impedance analysis (BIA) was performed to determine body composition parameters before, in the middle of, and at the end of RT. All patients received nutritional counselling and majority of them (94.6%) received oral nutritional supplement (ONS) during RT or chemoradiotherapy. If a patient consumed ≥75% of the recommended energy and protein intake via ONS and regular food, he/she was considered to be “compliant” (n=18), while those who failed to meet this criteria were considered to be “noncompliant” (n=30). Results. Body mass index, weight, fat percentage, fat mass, fat free mass, and muscle mass did not decrease significantly over time in compliant patients, but in noncompliant patients, all of these indices decreased significantly from baseline compared to the end of treatment (p<0.001). Hand grip strength did not differ significantly between the two groups at baseline and over time in each group. When retrospectively evaluated, heavy mucositis was less commonly observed in compliant than noncompliant patients (11.1% versus 88.9%, resp.) (p<0.009). Conclusion. We conclude that body composition parameters were better in head and neck cancer patients considered as compliant with nutritional counselling than noncompliant ones during RT period.